Rezension von: Gräter, Carlheinz, Der Neckar - Blümcke, Martin (Württembergisch Franken, 1979)
Carlheinz Gräter: Der Neckar. Mit Fotos von Joachim Feist, Albrecht Brugger u.a., Stuttgart: Theiß, 1977. 227 S.